PENGARUH KOMPETENSI GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN IKLIM ORGANISASI SEBAGAI MODERASI PADA SMK NEGERI 2 PATI - Sutriyono, Toto; Sunarto, Sunarto (Jurnal Ilmiah Telaah Manajemen, 2017)
This research aimed to analyze the influence of teacher competence and motivation to the Teacher Performance with Organizational Climate as moderation. The population is made the object of research is all teachers of SMK Negeri 2 Pati Empirical research using quantitative descriptive research method with sampling technique using census method. Data were taken from primary data through a questionnaire with data analysis using multiple linear regression equation. The research proves that the Variables Teacher Competence ,Motivation and Organizational Climate variables significant positive effect on the dependent variable of teacher performance. But the climate organization does not moderate influence on the Teacher Competence Variables and Motivation variable to variable Teacher Performance. Keywords: Teachers Competency, Motivation, Organizational Climate and Teachers Performance.